Association of Anti-TNF Therapy With Increased Risk of Acute Cholangitis in Patients With Primary Sclerosing Cholangitis. Issue 10 (10th December 2020) - Kulkarni, Chiraag; Murag, Soumya; Cholankeril, George; Fardeen, Touran; Mannalithara, Ajitha; Lerrigo, Robert; Kamal, Ahmad; Ahmed, Aijaz; Goel, Aparna; Sinha, Sidhartha R
Abstract: Background: Patients with primary sclerosing cholangitis (PSC) are at increased risk of developing acute cholangitis. The majority of patients with PSC have comorbid inflammatory bowel disease, and many take immunosuppressive medications. The epidemiological risks for the development of acute cholangitis in patients with PSC, including the impact of immunosuppressive therapy, are unknown. Methods: We conducted a 2-center, retrospective cohort study using data from 228 patients at Stanford University Medical Center and Santa Clara Valley Medical Center (CA), a county health care system. Patient demographics, medications, PSC disease severity, and inflammatory bowel disease status were extracted. Using stepwise variable selection, we included demographic and covariate predictors in the multiple logistic regression model assessing risk factors for cholangitis. Time-to-event analysis was performed to evaluate specific immunosuppressive medications and development of cholangitis. Results: Thirty-one percent of patients had at least 1 episode of acute cholangitis (n = 72). Anti-tumor necrosis factor (TNF) therapy was associated with increased odds of acute cholangitis (odds ratio, 7.29; 95% confidence interval, 2.63-12.43), but immunomodulator use was protective against acute cholangitis (odds ratio, 0.23; 95% confidence interval, 0.05-0.76). Anti-TNF therapy was associated with decreased time-to-cholangitis, with a median time of 28.4 months; in contrast, only 11.1% of patients who were prescribed immunomodulators developed cholangitis over the same time period ( P < 0.001). Conclusions: Our observations suggest that classes of immunosuppressive medications differentially modify the odds of acute cholangitis. Biologic therapy, ie, anti-TNF therapy, was shown to have significantly higher odds for patients developing acute cholangitis whereas immunomodulator therapy was shown to have a potential protective effect. These findings may help guide physicians in decision-making for determining appropriate immunosuppressive therapy.